An investigation on the microstructure and defects in the mechanically milled Cu and Fe powders. Issue 1 (21st October 2014) - Mojtahedi, M.; Goodarzi, M.; Aboutalebi, M. R.; Soleimanian, V.
Abstract : The microstructural characteristics of mechanically milled (MM) iron (Fe) and copper (Cu) powders are investigated by means of various X-ray crystallography analysis methods. The conventional Williamson–Hall and Warren–Averbach methods are used besides the modified Williamson–Hall, the modified Warren–Averbach, and the Variance approaches, in proper cases. Afterward, the obtained crystallite size and dislocation density are used to calculate the stored energy in the nanostructured powders. For this aim, a new geometrical approach is developed which can consider three-dimensional crystallites and the thickness of boundaries between them. Moreover, the released energy during annealing of MM Cu and Fe powders is measured using differential scanning calorimetry. The results of line broadening analysis and geometrical modelling are combined to the calorimetry of a room temperature aged Cu powder. In this way, the thickness of grain boundary in the nanostructured Cu is calculated to be 1.6 nm.